Equity valuation: SONAE SGPS, SA - Martins, João Carlos Ferreira Monteiro (2017)
Valuing a company is a complex challenge. The process can be supported by several different approaches and theoretical models. Also, it is a component whose results are open to diverse interpretations since it requires the development of assumptions and projections. It is a field that does not generate a solid agreement between experts. However, it is a fundamental tool that both individuals and organizations are increasingly using when making investment decisions. This project aims to defy the issue of valuing a business with the aid of some theoretical models, selected for being considered the most appropriate according to academic and scientific literature. Hence, the primary purpose of this study is to provide an accurate and realistic valuation of Sonae SGPS, SA, one of the largest Portuguese companies, achieving a market price for the company’s shares on the December 31st of 2015. The present project first explores and outlines important information regarding models and concepts used in order to obtain the best possible valuation for Sonae. Second, to acquaint the reader about Sonae, a contextualization of the company and the sectors it operates is displayed. Finally, all the assumptions, models, results and further conclusions of this study are presented. On the basis of the results of this research it can be concluded that Sonae shares are priced below its true value.